Understanding visitor awareness and knowledge of marine parks: Insights from the Ningaloo Coast, Australia. (1st August 2022) - Tuohy, P.; Cvitanovic, C.; Shellock, R.J.
Abstract: Marine Protected Areas (MPAs) are a key policy instrument used for the protection of ocean and coastal environments. However, many MPAs are currently falling short of their intended objectives. Studies show that meaningful public engagement can assist in optimising the outcomes of an MPA by improving stakeholder knowledge, support, and social license, and thus improving voluntary compliance with local MPA regulations. Ensuring more meaningful engagement, however, requires a context specific understanding of how different stakeholder groups understand the MPA, how they acquire that knowledge, and how information delivery can be tailored more effectively to reach the target audience. To that end, this study employed a quantitative survey to explore stakeholder awareness and knowledge of the Ningaloo Marine Park (NMP), a multi-use marine park on the west Australian coastline. Specifically, we surveyed visitors (i.e., tourists) to the Ningaloo region to understand their awareness of the NMP, their knowledge of the marine zoning regulations, and their access to information (N = 169). Results suggest that visitors to the region exhibit low levels of awareness of the primary management bodies, and of the presence of zoning regulations in the NMP. There was also a significant gap in the perceived level of protection afforded by the NMP compared to the actual protection, with visitors believing that the MPA provides more protection of the marine environment than it does in practice. These findings highlight a need for future regional communication strategies to be focused on improving the overall awareness and knowledge of the NMP among visitors through clear, consistent and accessible information. Specifically, visitors indicated that moving forwards, they would like to access this information through visitor centres, on local signage and on websites. The results of this study provide valuable insights for local marine park managers and decision-makers to improve existing communication strategies in order to maximise the ecological, social and economic outcomes of the NMP. These insights also have a wider application for improving ongoing public engagement with MPAs globally, which is particularly important given the rapid designation of MPAs to meet the global target of 30% of global oceans protected by 2030. Highlights: Visitor survey to assess awareness and knowledge of Ningaloo Marine Park (NMP). Participants had low levels of awareness of management bodies and zoning regulations. Participants believed the NMP provides more protection than it does in practice. Future communications should improve awareness and knowledge of zoning regulations. Communication efforts should be via visitor centres, on signage and on websites.